2016
DOI: 10.1038/ja.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic potential of sesquiterpene synthases: product profiles of Egyptian Henbane premnaspirodiene synthase and related mutants

Abstract: The plant terpene synthase (TPS) family is responsible for the biosynthesis of a variety of terpenoid natural products possessing diverse biological functions. TPSs catalyze the ionization and, most commonly, rearrangement and cyclization of prenyl diphosphate substrates, forming linear and cyclic hydrocarbons. Moreover, a single TPS often produces several minor products in addition to a dominant product. We characterized the catalytic profiles of Hyoscyamus muticus premnaspirodiene synthase (HPS) and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“… FPP cyclization reactions leading to the formation of major products 5-epi-aristolochene and premnaspirodiene, as well as alternative cyclization products generated by cyclase mutants classified by Noel and colleagues as follows: 309 class A products (gray) result from quenching of early carbocation intermediates; class B products (yellow) derive from the eudesmane cation in the absence of any alkyl migrations; class C products (C1, blue; C2, red; C3, green) derive from three different alkyl migrations in the eudesmane cation; and class D products (purple) derive from the ( cis,trans )-farnesyl cation. Reprinted with permission from ref ( 315 ). Copyright 2016 Macmillan Publishers Ltd. …”
Section: Class I Terpenoid Cyclasesmentioning
confidence: 99%
“… FPP cyclization reactions leading to the formation of major products 5-epi-aristolochene and premnaspirodiene, as well as alternative cyclization products generated by cyclase mutants classified by Noel and colleagues as follows: 309 class A products (gray) result from quenching of early carbocation intermediates; class B products (yellow) derive from the eudesmane cation in the absence of any alkyl migrations; class C products (C1, blue; C2, red; C3, green) derive from three different alkyl migrations in the eudesmane cation; and class D products (purple) derive from the ( cis,trans )-farnesyl cation. Reprinted with permission from ref ( 315 ). Copyright 2016 Macmillan Publishers Ltd. …”
Section: Class I Terpenoid Cyclasesmentioning
confidence: 99%
“…[233] Ad etailed analysis of the product profiles of TEAS and HPS has led to the characterisation of several side products and demonstrated that TEAS produces minor amountso f95, [234] while HPS generates small quantities of 93 from FPP. [235] Domain swapping experiments between TEAS and HPS resulted in enzymev ariants making mixtures of 93 and 95 and allowed the identification of domains that conferred specificity for these two products. [236] After the crystal structure of TEAS had become available, as ystematic and rational approach targeting nine selected residues within andn ear the active site in all 2 9 = 512 combinations forafunctional interconversion between TEAS and HPS wass urveyed.…”
Section: Rearranged Eudesmanes From H4mentioning
confidence: 99%
“…A detailed analysis of the product profiles of TEAS and HPS has led to the characterisation of several side products and demonstrated that TEAS produces minor amounts of 95 , [234] while HPS generates small quantities of 93 from FPP [235] . Domain swapping experiments between TEAS and HPS resulted in enzyme variants making mixtures of 93 and 95 and allowed the identification of domains that conferred specificity for these two products [236] .…”
Section: Rearranged Eudesmanesmentioning
confidence: 99%
“…Interestingly, 138 potential genes encoding these enzymes were identified by blasting the known protein database, including acetyl-CoA-acetyltransferase (AACT); hydroxymethylglutaryl-CoA synthase (HMGS); hydroxymethylglutaryl-CoA reductase (HMGR); mevalonate kinase (MK); phosphomevalonate kinase (PMK); diphosphomevalonate decarboxylase (MPD); 1-deoxy- D -xylulose-5-phosphate synthase (DXS); 1-deoxy- D -xylulose-5-phosphate reductoisomerase (DXR); 2- C -methyl- D -erythritol 4-phosphate cytidylyltransferase (MCT); 4-diphosphocytidyl-2- C -methyl- D -erythritol kinase (CMK); 2- C -methyl- D -erythritol 2,4-cyclodiphosphate synthase (MCS); ( E )-4-hydroxy-3-methylbut-2-enyl-diphosphate synthase (HDS); 4-hydroxy-3-methylbut-2-enyl diphosphate reductase (HDR); isopentenyl-diphosphate delta-isomerase (IPPI) ( Table 2 , Figure 1 , and Supplementary Table S3 ). Finally, IPP and isomer DMAPP synthesize GPP and FPP by geranyl diphosphate synthase (GPPS) and farnesyl diphosphate synthase (FPPS), respectively, which are then diverted to different mono- (e.g., α-pinene) and sesqui-terpenes (e.g., β-caryophyllene), respectively, after a single step enzymatic reaction mediated by TPS (Keszei et al, 2010; Koo et al, 2016; Piechulla et al, 2016) ( Figure 1 ). Therefore, identifying the function of TPS enzymes in the last step are important for understanding the molecular mechanism of terpenoid synthesis in R. tomentosa .…”
Section: Resultsmentioning
confidence: 99%
“…GPP and FPP serve as substrates for terpene synthases (TPSs) for synthesizing mono- and sesqui-terpenes, respectively (Yahyaa et al, 2015; Despinasse et al, 2017), during which the synthesis of monoterpenes is initiated by GPP dephosphorylation and ionization to geranyl carbocation, while the synthesis of sesquiterpene starts with FPP ionization to a farnesyl cation (Degenhardt et al, 2009; Huang et al, 2010). This is then followed by a series of complex chemical mechanisms involving isomerizations, cyclizations, and rearrangements catalyzed by TPSs, which finally generate structurally diverse terpenoids (Keszei et al, 2010; Koo et al, 2016; Piechulla et al, 2016) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%